Phylogenetic study of some bifurcate hairy sections belonging to Astragalus L. with emphasis on sect. Ornithopodium, based on morphological and molecular data in Iran - Abbas Saidi; Reza Sheikh Akbari Mehr; Shahrokh Kazempour Osaloo; Ali Asghar Maassoumi; Majid Ghorbani Nahooji (تاکسونومی و بیوسیستماتیک, 2012)
In this research, total of 15 species belonging to Astragalus section Ornithopodium as well as its closely related ones were analyzed using morphological and molecular data. A. frigidus and A. stocksii were selected as outgroups based on previous studies. Based upon our results, species of sect. Ornithopodium along with those of sect. Onobrychoidei were placed within a single large clade with high support and are closely related taxa. Species from section Dissitiflori formed a distinct clade from the two other studied sections. Based on our molecular and morphological data, Astragalus pravitzii Podlech, which had been recently transferred to the section Ornithopodium from the section Dissitiflori, was not affiliated with that section.